WHEN ENGLISH LEADS: REFRAMING EYL IN THE CONTEXT OF BAHASA INDONESIA STRUGGLES AT KINDERSTATION PRIMARY - Budiono, Gracendy Aluz Clarita (Universitas PGRI Palembang, 2025)
This study investigates the influence of the English-based International Primary Curriculum (IPC) on Indonesian language development at Kinderstation Primary, a National Plus school in Indonesia. Focusing on the dynamics of early bilingualism, it explores how the dominance of English from a young age impacts students’ linguistic equilibrium. Employing a qualitative case study design, data were collected through classroom observations, interviews with teachers and parents, questionnaires, and student language samples. Findings reveal that lower-grade students (grades 1–2) remain in a transitional phase, predominantly using Indonesian in both learning and interaction. In contrast, upper-grade students (grade 3 and above) exhibit strong English proficiency and increasingly favor English for both academic and everyday contexts. Notably, there is a marked reduction in students’ confidence and active use of Indonesian. While most parents did not express concern, they emphasized the importance of balanced bilingualism. The study underscores the need for integrated bilingual instruction, cultural reinforcement, and curriculum refinement to ensure that students grow as globally competent individuals without compromising their national language and identity. These insights offer critical implications for English for Young Learners (EYL) practices within internationalized educational settings in non-English dominant contexts.